1997
DOI: 10.1152/ajpendo.1997.273.1.e99
|View full text |Cite
|
Sign up to set email alerts
|

Mixed muscle protein synthesis and breakdown after resistance exercise in humans

Abstract: Mixed muscle protein fractional synthesis rate (FSR) and fractional breakdown rate (FBR) were examined after an isolated bout of either concentric or eccentric resistance exercise. Subjects were eight untrained volunteers (4 males, 4 females). Mixed muscle protein FSR and FBR were determined using primed constant infusions of [2H5]phenylalanine and 15N-phenylalanine, respectively. Subjects were studied in the fasted state on four occasions: at rest and 3, 24, and 48 h after a resistance exercise bout. Exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
990
4
33

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(1,073 citation statements)
references
References 13 publications
46
990
4
33
Order By: Relevance
“…In hemodialysis patients, we used different types of exercise to improve muscle function and the balance between muscle protein synthesis and breakdown (10,23,24). We found that endurance training reduced the level of the actin fragment in muscle of hemodialysis patients to values that were found in the muscle of normal adults (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…In hemodialysis patients, we used different types of exercise to improve muscle function and the balance between muscle protein synthesis and breakdown (10,23,24). We found that endurance training reduced the level of the actin fragment in muscle of hemodialysis patients to values that were found in the muscle of normal adults (Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Resistance exercise is important and well known in development of muscle mass (hypertrophy). In humans, resistance exercise increases protein synthesis [97][98][99][100][101][102][103][104][105][106] and improves protein balance during the recovery phase in the skeletal muscle, 8,107,108 but not during acute bouts of resistance exercise. 109 Similar to resistance exercise, low intensity aerobic training 110 causes a significant increase in fractional synthetic rate in the leg muscle.…”
Section: A Correspondence Between Immune and Muscle Cellsmentioning
confidence: 99%
“…8 Thus, exercise can be used to follow the cross-regulation of protein breakdown and rebuilding, including novel regulatory paths that might exist. We propose that there is such a novel, previously unappreciated regulated crosstalk between heat shock-governed protein synthesis and folding and the protein degradation state driven by autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…This effect on protein synthesis appears to be shared with the anabolic effects of amino acids (particularly leucine) and insulin (10,11) . In addition, HMB attenuates the induction of the ubiquitin -proteosome proteolytic pathway caused by proteolysis-inducing factor, lipopolysaccharide and angiotensin II, resulting in a decrease in muscle protein breakdown (12 -14) .Human studies have shown a positive effect of resistance exercise on muscle protein synthesis as early as 1 -2 h postexercise and lasting up to 48 h (15,16) . Studies have also shown that the timing of nutrient availability is critical for maximal post-exercise stimulation of protein synthesis as well as blunting of protein breakdown (17) .…”
mentioning
confidence: 99%